2022
DOI: 10.1002/tpg2.20270
|View full text |Cite
|
Sign up to set email alerts
|

Development of molecular inversion probes for soybean progeny genomic selection genotyping

Abstract: Increasing rate of genetic gain for key agronomic traits through genomic selection requires the development of new molecular methods to run genome‐wide single‐nucleotide polymorphisms (SNPs). The main limitation of current methods is the cost is too high to screen breeding populations. Molecular inversion probes (MIPs) are a targeted genotyping‐by‐sequencing (GBS) method that could be used for soybean [Glycine max (L.) Merr.] that is both cost‐effective, high‐throughput, and provides high data quality to scree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The ability to reevaluate the same loci with high read coverage also reduces the need for imputation and supports comparisons of samples across marker datasets. Another benefit of this technology lies in its modularity: Users may add or exchange probe designs to fit their needs, making it possible to produce future iterations of the existing DArTag panels that better represent their own core germplasm diversity, or add specific probes at predictive loci (e.g., R‐genes) to perform MAS and genomic prediction with a single platform (Wang et al., 2023). We were able to identify candidate SNPs supporting designs with high probabilities of subgenome‐specific probe targeting across most of the FaRR1 physical genome landscape, demonstrating the abundance of targets that can be assayed with the technology (Figure 5; Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability to reevaluate the same loci with high read coverage also reduces the need for imputation and supports comparisons of samples across marker datasets. Another benefit of this technology lies in its modularity: Users may add or exchange probe designs to fit their needs, making it possible to produce future iterations of the existing DArTag panels that better represent their own core germplasm diversity, or add specific probes at predictive loci (e.g., R‐genes) to perform MAS and genomic prediction with a single platform (Wang et al., 2023). We were able to identify candidate SNPs supporting designs with high probabilities of subgenome‐specific probe targeting across most of the FaRR1 physical genome landscape, demonstrating the abundance of targets that can be assayed with the technology (Figure 5; Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to high concordance between alignment‐based genotypes and WGS genomic variant genotypes, we found that the mid‐density 3K and 5K DArTag panels produce highly similar kinship estimates to those produced using the 50K SNP array markers. Accurate kinship estimates should support correspondingly high accuracy for predicting genomic breeding values (Habier et al., 2009; Wang et al., 2023). Beyond genotype calling accuracy, the 3K and 5K DArTag panels target SNPs that reflect significant genetic diversity across a range of domesticated strawberry germplasm and should therefore be useful for genomic prediction and forensic identification in most breeding populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations